The population growth and the nutritional status of Moina macrocopa feed with rice bran and cassava bran suspensions - Mubarak, Ahmad Shofy; Jusadi, Dedi; Junior, Muhammad Zairin; Suprayudi, Muhammad Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT Moina macrocopa culture density can be improved by optimizing the fecundity, and somatic growth through the regulation of quality and quantity of feed. The purpose of this study were to determined how to use effectively the rice bran and cassava bran Manihot utilisima suspension on Moina, based on population, neonates production, adult percentage, biomass, metabolisme and nutritional state. In this study, Moina were cultured for eighth days using four concentrations of rice bran suspension and three concentrations of cassava suspension. This research found that M. macrocopa culture with rice bran suspension has higher population, neonates production, adult percentage and biomass than its culture with cassava bran suspension (P<0.05). This study also found that Moina culture with rice bran suspension has higher total value of RNA, total value of DNA, the ratio RNA/ DNA, FCR, and concentration of protein and amino acid than Moina culture with cassava bran suspension. Treatment D with the initial rice bran suspension concentration was 0.3 mL/L and was increased starting the second day and the end concentration on the eighth day was 1.2 mL/L has highest peak population of Moina 17,975 ind/L in seventh day, weight wet biomass 439 mg/L in eighth day and lower FCR 0.94. Keywords: suspension, rice bran, cassava, population, ratio RNA/DNA ABSTRAK Kepadatan populasi dalam budidaya Moina macrocopa dapat ditingkatkan dengan mengoptimalkan fekunditas dan pertumbuhan somatik melalui pengaturan kualitas dan kuantitas pakan. Penelitian ini bertujuan untuk menganalisis efektifitas pengunaan pakan suspensi dedak dan tepung ketela pohon Manihot utilisima dalam budidaya M. macrocopa terhadap populasi, produksi anak per induk, persentase dewasa, biomasa, FCR, dan metabolismenya (asam amino, DNA, RNA, dan RNA/DNA). Di dalam penelitian ini, M. macrocopa dibudidayakan selama delapan hari menggunakan empat konsentrasi suspensi dedak dan tiga konsentrasi suspensi tepung ketela pohon. Hasil penelitian ini menunjukkan bahwa, budidaya M. macrocopa dengan pakan suspensi dedak menghasilkan populasi, produksi anak/induk, persentase dewasa dan biomasa yang lebih tinggi dibandingkan budidaya Moina dengan pakan suspensi ketela pohon (P<0,05). Budidaya M. macrocopa dengan pakan suspensi dedak juga menghasilkan total RNA, total DNA dan nisbah RNA/DNA, konsentrasi protein, dan asam amino yang lebih tinggi dibandingkan Moina dengan pakan suspensi ketela pohon. Perlakuan D dengan pakan suspensi dedak awal 0,2 mL/L dan meningkat mulai hari kedua dengan konsentrasi hari kedelapan 1,2 mL/L menghasilkan puncak populasi tertinggi pada hari ketujuh sebanyak 17.975 ind/L, berat basah biomasa hari kedelapan kultur 439 mg/L, dan FCR yang rendah yaitu 0,94. Kata kunci: suspensi, dedak, ketela pohon, populasi, nisbah RNA/DNA